Aktivitas Antibakteri Ekstrak Daun Rivina humilis L. Terhadap Staphylococcus aureus dan Pseudomonas aeruginosa - Yuliani, Ririn Kholifatu; Ilma, Nur Malika; Tufahati, Nadhira; Salimah, Azizah Zahratus; Aji, Oktira Roka (JST (Jurnal Sains dan Teknologi), 2025)
Rivina humilis (getih-getihan) is a wild plant that contains bioactive compounds that have the can to be used as antibiotics. This study aims to determine the antibacterial activity of ethanol extract of getih-getihan leaves against Staphylococcus aureus (Gram positive) and Pseudomonas aeruginosa (Gram negative) bacteria through in vitro experimental research. The subject used in the study was getih-getihan (Rivina humilis) leaves which were fresh and good without any disease. Data collection methods were carried out through laboratory experiments including extraction, metabolic analysis using LC-HRMS, antibacterial testing using disc diffusion, MIC and MBC. Data were analyzed using ANOVA and Duncan's post-hoc test with a significant value of p<0.05. The results of ethanol extract of getih-getihan leaves showed flavonoids, phenols, triterpenoids, amino acids, fatty acids, and carboxylic acids. The extract is can to inhibit and kill both bacteria, which is indicated by the presence of an inhibition zone, a decrease in absorbance, and no colony growth on the test media. In conclusion, ethanol extract of getih-getihan leaves has antibacterial activity against S. aureus and P. aeruginosa. The implication is that ethanol extract of getih-getihan leaves has the potential to be developed as a natural antibacterial agent that supports alternative treatment against bacterial infections against S. aureus and P. aeruginosa.